OLAM TIL ORQALI SHAKLLANADI - Qodirova, F.Q. (SCIENCE and SOCIETY, 2023)
Language is a means of communication and expression and is often acquired "naturally" in relationships with loved ones and society at large. It helps us question the world, communicate and develop our beliefs, validate our beliefs, and confirm or refute our claims.
Keywords: means of communication; language; linguistics; sign; sentence